LACTOGENIC ACTIVITY OF RATS STIMULATED BY GUNNERA PERPENSA L. (GUNNERACEAE) FROM SOUTH AFRICA - Simelane, M B. C; Lawal, O A; Djarova, T G; Musabayane, C T; Singh, M; Opoku, A R (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Gunnera perpensa L. (Gunneraceae) is a medicinal plant used by Zulu traditional healers to stimulate milk production. The effect of an aqueous extract of the rhizome of the plant on milk production in rats was investigated. Female lactating rats that received oral doses of the extract of G.perpensa significantly (p<0.05) produced more milk than controls. The plant extract did not however, significantly influence the levels of prolactin, growth hormone, progesterone, cortisol, ALT, AST and albumin in the blood. The mammary glands of rats treated with the extract showed lobuloalveolar development. The extract (0.8 μg/ml) was also found to stimulate the contraction of the uterus and inhibit (23%) acetylcholinesterase activity. The cytotoxicity of the extract (LC50) to two human cell lines (HEK293 and HepG2) was 279.43 µg/ml and 222.33µg/ml, respectively. It is inferred that the plant extract exerts its activity on milk production and secretion by stimulating lobuloalveolar cell development and the contraction of myoepithelial cells in the alveoli. It is concluded that Gunnera perpensa contains constituents with lactogenic activity that apparently contribute to its effectiveness in folk medicine.